Gerakan Sosial Intelektual Muslim Organik dalam Transformasi Sosial - Agus Afandi (Religió: Jurnal Studi Agama-agama, 2011)
Antonio Gramsci’s idea of organic intellectuals that dedicate their life to improve social life has been actually inherited within Indonesian Muslim intellectuals. The main characteristic of them is not conceptualizing and publishing their own interest in the context of academic field, but expressing and advocating social aims. This article attempts to capture Indonesian organic intellectual movement was fashioned from the era of HOS Cokroaminoto in colonial era until the existence of Non-Governmental Organization (NGO) in the present time. The history of Indonesia has witnessed that such movement has actively promoted social purposes and aspirations. Although, in its progress, organic intellectual movement is always challenged by the regime (policy oriented studies), it always comes with its own academic-emancipatory explanation for social problems. After Reformation Era, the goal of this movement focuses on advocating society against global capitalism which is expressed in—for example—World Trade Organization (WTC) and Multi-National Corporation (MNC). Another finding of this paper is that there are many NGOs in Indonesia based on Islamic values although their activists do not work on the name of Islam. The reason behind this view is that because all Muslim activists work on religious normative exercise social, economic, political, cultural, environment problems.